Pengaruh Pendapatan dan Biaya Operasional terhadap Laba Bersih (studi kasus pada Perusahaan Manufaktur Sektor Industri Dasar dan Kimia yang terdaftar di BEI periode 2012-2016). - Gusganda Muria (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
This study was conducted in Indonesia Stock Exchange. The phenomenon that occurs is that Net Income tends to decline during the period 2012-2016, which is coupled with the decrease in Revenue and increase in Operational Cost. The purpose of this study is to determine the effect of Revenue and Operational Cost on Net Income in Industry and Chemical Companies periode 2012-2016.This study uses descriptive analysis and verification with quantitative approach that is 11 industry and chemical company listed on the Stock Exchange data obtained are secondary data from the annual publication of financial statements consists of income over 5 years, ie the year 2012 to 2016. Technical analysis of data used is the technique of multiple linear regression analysis. Based on the result of this study showed that thitung with ttabel is equal to 16,082 > 2,005, thitung is bigger than ttabel that mean as partially there are effect revenue to net income, and result of partial research of operational cost to net income show thitung with ttabel is equal to -10,999 < 2,052, thitung is lowwer than ttabel that also means as partially there are negative effect operational cost to net income. The study result of the simultaneously shows the value of Fhitung with Ftabel is equal to 133,398 > 3,175, Fhitung is bigger than Ftabel that mean there are simultant influence of revenue and operational cost to net income. Keywords: Operational Cost, Revenue, Net Income.